Constitutional guarantee of the right to judicial protection in disputes concerning the invalidity of a will as grounds for the acquisition of property rights in Ukraine - Олькіна, Олена Володимирівна; Олькіна, О. В.; Олькина, Елена Владимировна; Olkina, Olena V.; Дробуш, Ірина Вікторівна; Дробуш, І. В.; Дробуш, Ирина Викторовна; Drobush, Iryna V.; Водоп᾽ян, Тетяна Вікторівна; Водоп᾽ян, Т. В.; Водопьян, Татьяна Викторовна; Vodopian, Tetiana V.; et al. (Editorial Primmate S. A. S., 2019)
The authors of the article have carried out research in the field of ensuring the constitutional guarantees of the right to judicial protection in disputes concerning the invalidity of a will as a basis for acquiring property rights in Ukraine. The object of the study was the public relations that result from the recognition of a valid covenant. The subject of the study was the domestic regulations that provide the rights to judicial protection in disputes about the invalidity of the will. Constitution as the main law of Ukraine in Art. 3 establishes a guarantee under which the state is charged with the duty to assert and uphold human rights and freedoms, which is its primary duty. In case of violation, non-recognition or contestation human rights, the right to protection by a court is guaranteed by the Constitution. According to Art. 55 of the Constitution, the court protects human rights and freedoms. According to the results of the study, it was concluded that the norms of the Constitution, civil law and civil procedural legislation of Ukraine serve as the basis for a well-established generalization of jurisprudence in disputes about the invalidity of a will as a basis for acquiring property rights in Ukraine. However, the individual cases of individual courts of the national judicial system of Ukraine do not allow to claim the existence of a unified algorithm for the application of law-enforcement practice, agreed and recommended by the Supreme Court of Ukraine, which indicates the existence of possible controversial situations to resolve the problem further.

Автори статті сдійснили дослідження в сфері забезпечення конституційних гарантій права на судовий захист у спорах щодо недійсності заповіту як підстави набуття права власності в Україні. Об’єктом дослідження виступили суспільні відносини, які виникать внаслідок визнання надійсним заповіту. Предметом дослідження виступили вітчизнянні нормативно-правові акти, які забезпечують права на судовий захист у спорах щодо недійсності заповіту.Конституція як основний закон України в ст. 3 закріплює гарантію, згідно з якою на державу покладається обов’язок утвердження і забезпечення прав і свобод людини, що є її головним обов’язком. У випадку порушення, невизнання або оспорювання прав Конституцією гарантується право на захист судом. Відповідно до ст. 55 основного закону нашої держави судом захищаються права і свободи людини За результатами дослідження був зроблений висновок, що норми Конституції, цивільного та цивільного процесуального законодавства України слугують фундаментом усталеного узагальнення судової практики у спорах щодо недійсності заповіту як підстави набуття права власності в Україні. Разом із тим, поодинокі випадки судової практики окремих судів національної судової системи України не дають можливості стверджувати про існування єдиного алгоритму застосування правозастосовної практики, узгодженої і рекомендованої Верховним Судом України, що в свою чергу, свідчить про існування можливих спірних ситуацій щодо вирішення окресленої проблеми дослідження в подальшому.
Drobush I. Constitutional guarantee of the right to judicial protection in disputes concerning the invalidity of a will as grounds for the acquisition of property rights in Ukraine / I. Drobush, O. Olkina, T. Vodopian, I. But // Amazonia Investiga, Vol. 8. - Issue 22. – Editorial Primmate S. A. S., 2019. - Р. 766-772.
Keywords: constitutional guarantees; judicial protection; invalid will; property right; конституційні гарантії; судовий захист; недійсний заповіт; право власності; Research Subject Categories::LAW/JURISPRUDENCE